Сравнительный анализ аллельного состава микросателлитных локусов Brassica oleracea var. capitata L. - Шаптуренко, М.Н.; Печковская, Т.В.; Вакула, С.И.; Хотылева, Л.В. (Фактори експериментальної еволюції організмів, 2015)
Aims. White cabbage is characterized by high level of intraspecifi c heterogeneity due to some biological features that causes diffi culties for breeding at creation constant form and maintaining of their genetic typicality. Thus, we studied the effectiveness the set of SSR markers for both white cabbage diversity analysis and pure lines genotyping. Methods. Molecular-genetic studies were performed trough SSR PCR. Effectiveness the set of markers was evaluated by counting allelic richness, PICs, heterogeneity, allele frequencies using GenAlEx 6.5. To determine B.o.var capitata diversity with low and high variations, Jaccard dissimilarity index was estimated by Darwin software. Results. 15 microsatellite loci were characterized for the information content, allelic frequencies and heterogeneity level. The effective multiallelic markers (Bo20TR, BoDCTD4, BoPC34, BoPLD1, BoCalc) with high information content (PIC > 0.7) that could be successfully used for the analysis of inter- and intravarietal polymorphism B. oleracea var.capitata were defi ned. Based on the SSR-evaluation and subsequent clustering the genetic structure of breeding collection was established, which showed that most experimental forms have a common ancestral genetic basis, in spite of different origins. Conclusions. Proposed set of informative SSR markers is a useful tool for the selection of genetically constant material, as well as divergent cross combinations for the hybrid breeding. Identifi ed donors of rare SSR alleles potentially could be a source of valuable genetic segregation for further B. oleracea improvement. Keywords: Brassica oleracea var. capitata L. f. alba DC, genetic diversity, SSR.